An open‐label, dose‐escalation study to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of single doses of GSK2586881 in participants with pulmonary arterial hypertension. (20th January 2022) - Simon, Marc A.; Hanrott, Kate; Budd, David C.; Torres, Fernando; Grünig, Ekkehard; Escribano‐Subias, Pilar; Meseguer, Manuel L.; Halank, Michael; Opitz, Christian; Hall, David A.; Hewens, Deborah; Powley, William M.; et al.
Abstract: Preclinical and early clinical studies suggest that angiotensin‐converting enzyme type 2 activity may be impaired in patients with pulmonary arterial hypertension (PAH); therefore, administration of exogenous angiotensin‐converting enzyme type 2 (ACE2) may be beneficial. This Phase IIa, multi‐center, open‐label, exploratory, single‐dose, dose‐escalation study (NCT03177603) assessed the potential vasodilatory effects of single doses of GSK2586881 (a recombinant human ACE2) on acute cardiopulmonary hemodynamics in hemodynamically stable adults with documented PAH who were receiving background PAH therapy. Successive cohorts of participants were administered a single intravenous dose of GSK2586881 of 0.1, 0.2, 0.4, or 0.8 mg/kg. Dose escalation occurred after four or more participants per cohort were dosed and a review of safety, tolerability, pharmacokinetics, and hemodynamic data up to 24 h postdose was undertaken. The primary endpoint was a change in cardiopulmonary hemodynamics (pulmonary vascular resistance, cardiac index, and mean pulmonary artery pressure) from baseline. Secondary/exploratory objectives included safety and tolerability, effect on renin‐angiotensin system peptides, and pharmacokinetics. GSK2586881 demonstrated no consistent or sustained effect on acute cardiopulmonary hemodynamics in participants with PAH receiving background PAH therapy ( N  = 23). All doses of GSK2586881 were well tolerated. GSK2586881 was quantifiable in plasma for up to 4 h poststart of infusion in all participants and caused a consistent and sustained reduction in angiotensin II and a corresponding increase in angiotensin (1–7) and angiotensin (1–5). While there does not appear to be a consistent acute vasodilatory response to single doses of GSK2586881 in participants with PAH, the potential benefits in terms of chronic vascular remodeling remain to be determined.